Impact of Program Components on Perceived Organizational Support in Respiratory Care Education. - Ari, Arzu; Wang, Tiankai; Hudgins, Abbey M. (Respiratory Care, 2024)
BACKGROUND: Perceived organizational support has been linked to employee commitment and job satisfaction. Understanding the effects of perceived organizational support on employees allows leaders to improve employees' performance and the success of their organizations. The purpose of this study was to identify the perceived organizational support across different respiratory care education programs in the United States. METHODS: All chairs and program directors of bachelor's of science and master's of science degree respiratory care education programs in the United States were surveyed (N = 97). The Survey of Perceived Organizational Support was modified after written approval, and the final instrument included 31 items with a Likert scale (1 = strongly disagree, 7 = strongly agree). Descriptive statistics, multiple regression, and topic modeling were used for data analysis (P < .05). RESULTS: A total of 67 respondents responded to the perceived organizational support survey; a 69% response rate. They were satisfied with their job and committed to their institutions. They also reported that faculty salaries were equitable relative to the national average, and their institutions encouraged teamwork among faculty. The respondents' titles, total years of administrative experience, students' scores on the national credentialing therapist multiple choice examination (TMC), and institutions that offer both bachelor's of science and master's of science degree programs had a direct relationship with perceived organizational support in respiratory care education programs. Age and sex were inversely related to perceived organizational support. A topic modeling analysis based on the respondents' opinions about perceived organizational support showed that the respondents frequently mentioned the words support, institution, budget, year, nursing, and experience. The respondents emphasized the importance of support, institution marketing, their years of experience, and the program budget. They also mentioned that nursing programs overshadowed respiratory care education programs at their institutions. CONCLUSIONS: Age, sex, job title, years of administrative experience, students' TMC scores, and the type of programs offered impacted perceived organizational support by respiratory care directors. Student-, program- and participant-related factors can be used to improve perceived organizational support in respiratory care education.